Scratch-resistant photovoltaic cover plate glass capable of being strengthened as well as preparation method and application of scratch-resistant photovoltaic cover plate glass
By controlling the proportion and performance parameters of different components in the glass, a photovoltaic cover glass with high transmittance and scratch resistance was prepared, which solved the problem of vulnerability to the surface of the photovoltaic panel glass, extended the service life and improved the power generation efficiency.
Patent Information
- Application Number
- CN202411494255.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
The glass surface of photovoltaic panels is prone to cracks, scratches or perforations, which affects the power generation capacity and service life of solar panels.
By controlling the proportion and performance parameters of components such as silica, alumina, boron oxide, etc., a photovoltaic cover glass that can strengthen scratch resistance is prepared, with a transmittance of more than 91.3%, and is within the wavelength range of 200-1100nm Maintain high transmittance.
The high transmittance and good scratch resistance of the photovoltaic cover glass are achieved, which extends the service life of the photovoltaic panel and improves the power generation efficiency.
Smart Images

Figure CN119461838A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a photovoltaic cover glass capable of strengthening scratch resistance and a preparation method and application thereof, belonging to the technical field of glass. Background Art
[0002] Photovoltaic panels in photovoltaic power generation systems are usually composed of solar cells, glass, EVA and other materials. Glass is an important part of ensuring the normal power generation of solar cells. Because photovoltaic panels are used outdoors for a long time, the glass needs to have sufficient strength to protect the solar cells. However, due to the influence of the external environment, the glass surface of photovoltaic panels is prone to cracks, scratches or perforations. When the glass of photovoltaic panels is damaged, it will not only affect the power generation capacity of the solar panels, but also reduce the overall service life of the photovoltaic panels.
[0003] Scratches are usually caused by mechanical scratches. During installation, maintenance, use or transportation, the surface of the photovoltaic panel glass is accidentally touched, resulting in scratches. Weather factors, such as strong winds, floating sand, rain and other weather factors, can cause scratches on the surface of photovoltaic panels. In addition, pollutants such as sand, dust, and weeds can also cause scratches on the surface of photovoltaic panels.
[0004] There are several aspects to improve this problem:
[0005] Install protective film: Install a layer of protective film on the glass surface of the solar photovoltaic panel, so that even if the glass surface is scratched, it will not affect the power generation efficiency of the photovoltaic panel. There are many types of protective films, such as transparent plastic film, fiberglass film, etc. However, the film layer will reduce the glass transmittance to a certain extent, affecting the power generation efficiency.
[0006] Use high-hardness glass: The harder the glass of the solar photovoltaic panel is, the less likely it is to be scratched. Therefore, in order to avoid scratches on the surface of the solar photovoltaic panel, materials with higher glass hardness, such as tempered glass, laminated glass, etc., can be selected during the design and production process. Summary of the invention
[0007] In view of this, the main purpose of the present invention is to provide a photovoltaic cover glass with enhanced scratch resistance and its preparation method and application. The technical problem to be solved is to control the proportion and performance parameters between the various components so that the transmittance of the glass is greater than 91.3%; and it is not easy to be scratched and is suitable for photovoltaic cover.
[0008] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a photovoltaic cover glass with enhanced scratch resistance, which comprises, by mass percentage:
[0009] Silicon dioxide (SiO2) 78-82%; aluminum oxide (Al2O3) 1.8-2.5%; boron trioxide (B2O3) 12.8-13.7%; sodium oxide (Na2O) 1.0-4.5%; potassium oxide (K2O) 0-0.1%; lithium oxide (Li2O) 0.5-2%; magnesium oxide (MgO) 0-0.1%; calcium oxide (CaO) 0-0.1%; strontium oxide (SrO) 0-0.1%; barium oxide (BaO) 0-0.1%.
[0010] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0011] Preferably, the aforementioned photovoltaic cover glass with enhanced scratch resistance further comprises a clarifier in an amount less than or equal to 2 wt %.
[0012] Preferably, in the aforementioned reinforced scratch-resistant photovoltaic cover glass, the clarifier is selected from at least one of tin oxide (SnO2) and cerium oxide (CeO).
[0013] Preferably, in the aforementioned photovoltaic cover glass capable of strengthening scratch resistance, the mass percentage content of each component of the photovoltaic cover glass capable of strengthening scratch resistance also satisfies the following relationship:
[0014] 0.3≤Na2O / (Na2O+K2O+Li2O)≤0.9;
[0015] 0≤K2O / (Na2O+K2O+Li3O)≤0.05;
[0016] 0.1≤Li2O / (Na2O+K2O+Li4O)≤0.7.
[0017] Preferably, in the aforementioned photovoltaic cover glass capable of strengthening scratch resistance, each component of the photovoltaic cover glass capable of strengthening scratch resistance also satisfies the following relationship:
[0018] 1.0≤L≤2.0; L=C1*Al2O3%+C2*(Na2O%+K2O%+Li2O%)+
[0019] C3*(MgO%+CaO%+SrO%+BaO%)+C4*[Na2O / (Na2O%+K2O%+Li2O%)]+C
[0020] Wherein, Al2O3%, B2O3%, Li2O%, Na2O%, K2O%, MgO%, CaO%, SrO%, BaO%, respectively represent the mass percentage content of the component in the glass; 0.05≤C1≤0.2, -0.001≤C2≤0.001, 0.05≤C3≤0.2, -0.03≤C4≤-0.01, 1.0≤C≤1.5;
[0021] In the formula, C1=0.102, C2=-0.0009, C3=0.129, C4=-0.029, C=1.265.
[0022] Preferably, in the aforementioned photovoltaic cover glass with enhanced scratch resistance, the L value satisfies: 1.4≤L≤2.0.
[0023] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a photovoltaic cover glass capable of strengthening scratch resistance, comprising the following steps:
[0024] 1) According to mass percentage, 78-82% of silicon dioxide, 1.8-2.5% of aluminum oxide, 12.8-13.7% of boron trioxide, 1.0-4.5% of sodium oxide, 0-0.1% of potassium oxide, 0.5-2% of lithium oxide, 0-0.1% of magnesium oxide, 0-0.1% of calcium oxide, 0-0.1% of strontium oxide and 0-0.1% of barium oxide are mixed to obtain a uniform mixture;
[0025] 2) heating the mixture obtained in step 1) to melt at 1500-1600° C. for 2-4 hours, stirring 10-25 times in both forward and reverse directions using a platinum stirring rod, and then heating to 1550-1630° C. to clarify and homogenize for 1-3 hours; forming the mixture into a block glass, and then annealing the block glass at 450-500° C. for 1-4 hours, and naturally cooling the block glass to room temperature to obtain glass;
[0026] 3) heating the glass obtained in step 2) to 300-400° C. and keeping the temperature for 5-10 minutes; then placing the glass in a mixture of sodium nitrate and potassium nitrate for primary strengthening; cleaning the surface of the glass and placing the glass in potassium nitrate for secondary strengthening, and cooling to room temperature to obtain the reinforced scratch-resistant photovoltaic cover glass.
[0027] Preferably, in the aforementioned method for preparing the scratch-resistant photovoltaic cover glass, in step 3), the heating temperature is 300-400° C., and the insulation time is 5-10 minutes.
[0028] Preferably, in the aforementioned method for preparing the scratch-resistant photovoltaic cover glass, in step 3), the conditions for the primary strengthening are as follows: the mass ratio of sodium nitrate to potassium nitrate is 1.2-2.5; the temperature is 400-600° C., and the temperature is kept constant for 3-8 hours.
[0029] Preferably, in the aforementioned method for preparing the scratch-resistant photovoltaic cover glass, in step 3), the conditions for secondary strengthening are as follows: temperature is 400-600° C., and heat preservation is 0.2-2h.
[0030] The purpose of the present invention and the solution to its technical problems can also be achieved by the following technical measures. The present invention proposes a photovoltaic cover plate, which uses a photovoltaic cover plate glass with enhanced scratch resistance; the photovoltaic cover plate glass with enhanced scratch resistance comprises, by mass percentage:
[0031] Silicon dioxide 78-82%; aluminum oxide 1.8-2.5%; boron trioxide 12.8-13.7%; sodium oxide 1.0-4.5%; potassium oxide 0-0.1%; lithium oxide 0.5-2%; magnesium oxide 0-0.1%; calcium oxide 0-0.1%; strontium oxide 0-0.1%; barium oxide 0-0.1%.
[0032] Compared with the prior art, the photovoltaic cover glass with enhanced scratch resistance and its preparation method and application described in the present invention have the following beneficial effects:
[0033] The photovoltaic cover glass with enhanced scratch resistance of the present invention controls the ratio and performance parameters of the components so that the transmittance of the glass is greater than or equal to 91.32% and is not easily scratched.
[0034] The Vickers hardness of the scratch-resistant photovoltaic cover glass of the present invention is 830-839, without obvious scratches, and the average transmittance at 200-1100 nm is 91.32%-91.51%.
[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a transmittance curve of the scratch-resistant photovoltaic cover glass prepared in Example 1 of the present invention in the wavelength range of 200-1100nm. DETAILED DESCRIPTION
[0037] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a photovoltaic cover glass with enhanced scratch resistance and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0038] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0039] Some embodiments of the present invention provide a photovoltaic cover glass with enhanced scratch resistance, comprising, by mass percentage:
[0040] Silicon dioxide (SiO2) 78-82%; aluminum oxide (Al2O3) 1.8-2.5%; boron trioxide (B2O3) 12.8-13.7%; sodium oxide (Na2O) 1.0-4.5%; potassium oxide (K2O) 0-0.1%; lithium oxide (Li2O) 0.5-2%; magnesium oxide (MgO) 0-0.1%; calcium oxide (CaO) 0-0.1%; strontium oxide (SrO) 0-0.1%; barium oxide (BaO) 0-0.1%.
[0041] In some embodiments, optionally, the scratch-resistant photovoltaic cover glass further comprises a clarifier in an amount less than or equal to 2 wt %; the clarifier is selected from at least one of tin oxide (SnO 2 ) and cerium oxide (CeO).
[0042] The present invention can produce a photovoltaic glass cover plate with enhanced scratch resistance by precisely controlling the content of each component and the ratio between the components.
[0043] In the above technical scheme, in order to meet the high strength and high transmittance of photovoltaic cover glass, the glass of the present invention needs to use network formers such as silicon dioxide, aluminum oxide, and diboron trioxide as the basic skeleton. By studying the influence of different elements on the transmittance and strength of photovoltaic cover glass, a group of components suitable for photovoltaic cover glass is finally determined. In particular, in order to improve the transmittance of photovoltaic cover glass and make it have good glass forming properties, the present invention optimizes the content and proportion of sodium oxide, lithium oxide, magnesium oxide, calcium oxide, strontium oxide and barium oxide, and selects suitable content and proportion, which simultaneously meets the two necessary properties of high transmittance and glass forming properties. The content of silicon dioxide and boric acid in the glass is adjusted to improve the glass melting performance, and the content of aluminum oxide is adjusted to improve the crystallization performance and strength of the glass. In this way, the prepared photovoltaic cover glass can simultaneously meet good internal quality, high transmittance and strength.
[0044] The function and content of each component are as follows:
[0045] SiO2: Silicon dioxide (SiO2) is a glass-forming oxide, which forms an irregular continuous network with the structural unit of silicon-oxygen tetrahedron, becoming the skeleton of glass; SiO2 has high binding energy and is not easy to produce polarization under the action of external electric field, so it shows low dielectric constant and dielectric loss, and can also inhibit crystallization. However, when its content is greater than 82%, the glass is difficult to melt, the viscosity is very high, and it is difficult to clarify and homogenize; and when its content is less than 78%, glass cannot be formed. Therefore, the silicon oxide content of the present invention is limited to 78-82%.
[0046] B2O3: It is also a glass-forming oxide. Boron-oxygen tetrahedron [BO4] is a frame structure with a tight structure, which can effectively reduce the dielectric constant. However, if the B2O3 content continues to increase, when its content is greater than 13.7%, there will not be enough free oxygen in the glass, the boron-oxygen triangle [BO3] in the layered structure will increase, the boron-oxygen tetrahedron [BO4] content will decrease, the glass network structure will be loose, and the chemical properties will be unstable. Excessive boron oxide content will increase the volatilization and easily cause uneven glass composition; and when its content is less than 12.8%, the boron oxide content is too low, which will lead to high high-temperature viscosity of the glass and poor melting ability. Therefore, the B2O3 content of the present invention is controlled between 12.8 and 13.7%.
[0047] Al2O3 is an intermediate oxide. Since the aluminum-oxygen tetrahedron is more stable than the boron-oxygen tetrahedron, aluminum ions in the glass structure unit will first obtain free oxygen to form aluminum-oxygen tetrahedrons, and then the excess free oxygen will transform into boron-oxygen tetrahedrons with boron-oxygen triangles. If its content is less than 1.8%, aluminum oxide is too low to form glass; if its content is greater than 2.5%, aluminum oxide is too high to affect the formation of boron-oxygen tetrahedrons and reduce strength. The aluminum oxide content of the present invention is controlled between 1.8 and 2.5%.
[0048] Li2O, Na2O, and K2O are all alkali metal oxides. When a small amount of Li2O replaces Na2O, the small radius Li + It can fill the gaps in the glass network, causing the glass structure to become denser; as the amount of Li2O substitution increases, the free oxygen content decreases, resulting in a corresponding increase in the [BO3] content and a loose glass structure.
[0049] Therefore, the mass percentage content of the three needs to meet the following requirements:
[0050] 0.3≤Na2O / (Na2O+K2O+Li2O)≤0.9
[0051] 0≤K2O / (Na2O+K2O+Li3O)≤0.05
[0052] 0.1≤Li2O / (Na2O+K2O+Li4O)≤0.7
[0053] MgO, CaO, SrO, and BaO are all alkaline earth metal oxides. Their addition is beneficial to effectively reduce the high-temperature viscosity of glass, thereby improving the melting and formability of glass. However, excessive content will cause the glass network to break; in the present invention, MgO: 0-0.1%; CaO: 0-0.1%; SrO: 0-0.1%; BaO: 0-0.1%. Alkaline earth metals mainly reduce high-temperature viscosity. Too low content will lead to poor glass melting performance, while too high content of alkaline earth metals will cause phase separation.
[0054] The clarifier in the present invention improves the melting quality of the glass. At least one of CeO2 and SnO2 is added at a content of less than or equal to 2% to remove bubbles in the glass; if the content is greater than 2%, the excessive content will lead to excessive volatilization and reduced component uniformity.
[0055] Furthermore, the components of the photovoltaic cover glass capable of strengthening scratch resistance also satisfy the following relationship:
[0056] 1.0≤L≤2.0; L=C1*Al2O3%+C2*(Na2O%+K2O%+Li2O%)+
[0057] C3*(MgO%+CaO%+SrO%+BaO%)+C4*[Na2O / (Na2O%+K2O%+Li2O%)]+C
[0058] Wherein, Al2O3%, B2O3%, Li2O%, Na2O%, K2O%, MgO%, CaO%, SrO%, BaO%, respectively represent the mass percentage content of the component in the glass; 0.05≤C1≤0.2, -0.001≤C2≤0.001, 0.05≤C3≤0.2, -0.03≤C4≤-0.01, 1.0≤C≤1.5;
[0059] In the formula, C1=0.102, C2=-0.0009, C3=0.129, C4=-0.029, C=1.265.
[0060] The L value is preferably: 1.4≤L≤2.0, more preferably 1.4≤L≤1.6. Within this range, the ratio of aluminum oxide, alkaline earth metal elements and alkali metal elements in the photovoltaic glass is suitable for a photovoltaic glass composition with high transmittance and high strength.
[0061] After testing, the Vickers hardness of the photovoltaic cover glass is 830-839, there is no obvious scratch, and the average transmittance at 200-1100nm is 91.32%-91.51%.
[0062] Some embodiments of the present invention also provide a method for preparing a photovoltaic cover glass capable of strengthening scratch resistance, comprising the following steps:
[0063] 1) According to mass percentage, 78-82% of silicon dioxide (SiO2), 1.8-2.5% of aluminum oxide (Al2O3), 12.8-13.7% of boron trioxide (B2O3), 1.0-4.5% of sodium oxide (Na2O), 0-0.1% of potassium oxide (K2O), 0.5-2% of lithium oxide (Li2O), 0-0.1% of magnesium oxide (MgO), 0-0.1% of calcium oxide (CaO), 0-0.1% of strontium oxide (SrO) and 0-0.1% of barium oxide (BaO) are mixed to obtain a uniform mixture;
[0064] 2) adding the mixture obtained in step 1) into a platinum crucible, heating and melting it at 1500-1600° C. in a lifting furnace for 2-4 hours, stirring it in forward and reverse directions for 10-25 times using a platinum stirring rod, and then heating it to 1550-1630° C. for clarification and homogenization for 1-3 hours; adding it into a mold to form a block glass, and then annealing the block glass in an annealing furnace at 450-500° C. for 1-4 hours, and naturally cooling it to room temperature to obtain glass; wherein, a clarifier less than or equal to 2% of the mass of the photovoltaic cover glass capable of strengthening scratch resistance can be added during the clarification and homogenization.
[0065] 3) Preheating: heating the glass obtained in step 2) to 300-400° C. and keeping it warm for 5-10 minutes; primary strengthening: then placing the glass in a mixture of sodium nitrate and potassium nitrate, with a mass ratio of sodium nitrate to potassium nitrate of 1.2-2.5 (the content of sodium nitrate is greater than that of potassium nitrate), at a temperature of 400-600° C., and keeping the temperature constant for 3-8 hours; using hot water to wash the surface residue of the chemically strengthened glass, and then performing secondary strengthening, keeping the pure potassium salt at 400-600° C. for 0.2-2 hours, and cooling to room temperature to obtain the said reinforced scratch-resistant photovoltaic cover glass.
[0066] Some embodiments of the present invention further provide a photovoltaic cover plate, which adopts the aforementioned glass.
[0067] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0068] Example 1
[0069] This embodiment provides a method for preparing a photovoltaic cover glass capable of strengthening scratch resistance, which comprises the following steps:
[0070] According to the purity and moisture content of raw materials such as quartz sand, kaolin, boric acid, sodium carbonate, potassium carbonate, lithium carbonate, dolomite, limestone, strontium oxide and barium oxide, the raw materials are weighed and evenly mixed to obtain a uniform batching; then the batching materials are calculated according to the set ratio of Example 1 in Table 1, and the batching materials are weighed and mixed according to the batching material formula to obtain a uniform mixture I; the above mixture I is added to a platinum crucible, heated and melted at 1570° C. in a lifting furnace for 2 hours, and stirred 20 times in both forward and reverse directions using a platinum stirring rod, Then the temperature is raised to 1600°C for clarification and homogenization for 2 hours; the glass is added into a mold to be formed into a block glass, and then the block glass is annealed in an annealing furnace at 500°C for 2 hours, and naturally cooled to room temperature to obtain glass; the SiO2 is introduced through quartz sand, the Al2O3 is introduced through kaolin, the B2O3 is introduced through boric acid, the CaO is introduced through limestone, the MgO is introduced through dolomite, the Na2O, K2O, Li2O, etc. are introduced through their respective carbonates, and the others are introduced through their oxides;
[0071] The obtained glass was heated to 350°C and kept warm for 5 minutes; then the glass was placed in a mixture of sodium nitrate and potassium nitrate with a mass ratio of 6:4, the temperature was 410°C, and the temperature was kept constant for 3 hours; 80°C hot water was used to clean the surface residue of the chemically strengthened glass, and then secondary strengthening was carried out, pure potassium nitrate was kept warm at 420°C for 1 hour, and then directly cooled to room temperature to obtain the strengthened scratch-resistant photovoltaic cover glass, which is awaiting testing. Figure 1 The transmittance curve of the photovoltaic glass prepared in Example 1 of the present invention in the wavelength range of 200-1100nm is shown in FIG. Figure 1 It can be seen that it is better than strictly controlling the proportion and content of alumina, alkaline earth metals and alkali metals in the material according to the L value range. Its L value is 1.44, so its transmittance is 91.51% higher than others.
[0072] Examples 2-8 were carried out in a similar manner to Example 1, except that the amounts of constituent oxides were different, and at least one of CeO2 and SnO2 was added during the clarification and homogenization. The remaining conditions were the same as those of Example 1, see Table 1 for details.
[0073] The scratch-resistant photovoltaic cover glass of the above-mentioned embodiments 1-8 can be used to prepare photovoltaic cover plates.
[0074] Comparative Example 1:
[0075] This comparative example is a typical cover glass, and is prepared by a method similar to that of Example 1, except that the amount of raw materials used is different, and the other conditions are the same as those of Example 1, see Table 1 for details.
[0076] Comparative Example 2:
[0077] This comparative example is a typical cover glass, and is prepared by a method similar to that of Example 1, except that the amount of raw materials used is different, and the other conditions are the same as those of Example 1, see Table 1 for details.
[0078] The glasses prepared in Examples 1-8 and Comparative Examples 1-2 were subjected to the following tests. The specific test methods are as follows. The specific results are shown in Table 1:
[0079] (1) The scratch resistance test uses 100-grit sandpaper to reciprocate 1000 times on the polished glass surface and observe the scratches on the surface;
[0080] (2) Transmittance: The average transmittance of the glass samples at room temperature in the wavelength range of 200 to 1100 nm was measured using an ultraviolet-visible-near infrared spectrophotometer (U-4100).
[0081] Table 1
[0082]
[0083]
[0084]
[0085] From the data in Table 1, it can be seen that the L value of the scratch-resistant photovoltaic cover glass of Examples 1-8 of the present invention is 1.42-1.52, the Vickers hardness is 830-839, there is no obvious scratch, and the average transmittance at 200-1100nm is 91.32%-91.51%. + , unable to fill the gaps in the glass network, resulting in an insufficiently dense glass structure, and therefore its scratch resistance is inferior to that of Example 1-8. At the same time, since Comparative Example 1-2 does not have alkaline earth metal elements, its high temperature viscosity is relatively large, resulting in a lower transmittance after molding.
[0086] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0087] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0088] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A photovoltaic cover glass with enhanced scratch resistance, characterized in that: By mass percentage, it contains: Silicon dioxide 78-82%; aluminum oxide 1.8-2.5%; boron trioxide 12.8-13.7%; sodium oxide 1.0-4.5%; potassium oxide 0-0.1%; lithium oxide 0.5-2%; magnesium oxide 0-0.1%; calcium oxide 0-0.1%; strontium oxide 0-0.1%; barium oxide 0-0.1%.
2. The scratch-resistant photovoltaic cover glass according to claim 1, characterized in that: The scratch-resistant photovoltaic cover glass further comprises a clarifier in an amount of less than or equal to 2 wt %.
3. The scratch-resistant photovoltaic cover glass according to claim 1, characterized in that: The clarifier is selected from at least one of tin oxide and cerium oxide.
4. The photovoltaic cover glass with enhanced scratch resistance as claimed in claim 1, characterized in that: The mass percentage content of each component of the photovoltaic cover glass capable of strengthening scratch resistance also satisfies the following relationship: 0.3≤Na2O / (Na2O+K2O+Li2O)≤0.9; 0≤K2O / (Na2O+K2O+Li3O)≤0.05; 0.1≤Li2O / (Na2O+K2O+Li4O)≤0.
7.
5. The photovoltaic cover glass with enhanced scratch resistance as claimed in claim 1, characterized in that: The components of the scratch-resistant photovoltaic cover glass also satisfy the following relationship: 1.0≤L≤2.0; L=C1*Al2O3%+C2*(Na2O%+K2O%+Li2O%)+ C3*(MgO%+CaO%+SrO%+BaO%)+C4*[Na2O / (Na2O%+K2O%+Li2O%)]+C Wherein, Al2O3%, B2O3%, Li2O%, Na2O%, K2O%, MgO%, CaO%, SrO%, BaO%, respectively represent the mass percentage content of the component in the glass; 0.05≤C1≤0.2, -0.001≤C2≤0.001, 0.05≤C3≤0.2, -0.03≤C4≤-0.01, 1.0≤C≤1.5; In the formula, C1=0.102, C2=-0.0009, C3=0.129, C4=-0.029, C=1.
265.
6. The scratch-resistant photovoltaic cover glass according to claim 5, characterized in that: The L value satisfies: 1.4≤L≤2.
0.
7. A method for preparing a photovoltaic cover glass capable of strengthening scratch resistance, characterized in that: The following steps are involved: 1) According to mass percentage, 78-82% of silicon dioxide, 1.8-2.5% of aluminum oxide, 12.8-13.7% of boron trioxide, 1.0-4.5% of sodium oxide, 0-0.1% of potassium oxide, 0.5-2% of lithium oxide, 0-0.1% of magnesium oxide, 0-0.1% of calcium oxide, 0-0.1% of strontium oxide and 0-0.1% of barium oxide are mixed to obtain a uniform mixture; 2) heating the mixture obtained in step 1) to melt at 1500-1600° C. for 2-4 hours, stirring 10-25 times in both forward and reverse directions using a platinum stirring rod, and then heating to 1550-1630° C. to clarify and homogenize for 1-3 hours; forming the mixture into a block glass, and then annealing the block glass at 450-500° C. for 1-4 hours, and naturally cooling the block glass to room temperature to obtain glass; 3) heating the glass obtained in step 2) to 300-400° C. and keeping the temperature for 5-10 minutes; then placing the glass in a mixture of sodium nitrate and potassium nitrate for primary strengthening; cleaning the surface of the glass and placing the glass in potassium nitrate for secondary strengthening, and cooling to room temperature to obtain the reinforced scratch-resistant photovoltaic cover glass.
8. The method for preparing the scratch-resistant photovoltaic cover glass according to claim 7, characterized in that: In step 3), the heating temperature is 300-400° C., and the insulation time is greater than or equal to 5 minutes.
9. The method for preparing the scratch-resistant photovoltaic cover glass according to claim 7, characterized in that: In step 3), the conditions for the primary strengthening are as follows: the mass ratio of sodium nitrate to potassium nitrate is 6:4; the temperature is 400-600°C, and the constant temperature is 3-8h; the conditions for the secondary strengthening are as follows: the temperature is 400-600°C, and the temperature is kept for 0.2-2h.
10. A photovoltaic cover plate, characterized in that: The invention adopts a photovoltaic cover glass that can be strengthened to be scratch-resistant; the photovoltaic cover glass that can be strengthened to be scratch-resistant comprises, by mass percentage: Silicon dioxide 78-82%; aluminum oxide 1.8-2.5%; boron trioxide 12.8-13.7%; sodium oxide 1.0-4.5%; potassium oxide 0-0.1%; lithium oxide 0.5-2%; magnesium oxide 0-0.1%; calcium oxide 0-0.1%; strontium oxide 0-0.1%; barium oxide 0-0.1%.